Response to Javanese Tradition in Kiai Shaleh Daratâ€™s Writings - Ahmad, Nur (Teosofia: Indonesian Journal of Islamic Mysticism, 2017)
The process of Islamization of Java is totally obscure. Because of the dark history of their conversion into Islam, and of misleading information from some orientalists, some members of Muslim communities mistaken some rituals as animistic and un-Islamic. On the other extreme, ironically, theyconfuse creed that is in opposition to IslamwiththeIslamic orthodoxy. For the former, slametan is the perfect example, meanwhile, for the latter, sadjen becomes its representative. This paper aims to describe and analyzeKiai á¹¢aleh Daratâ€™s response to both slametan and sadjen, some abangan customs (adat)â€“ as Geertz would like to call â€“ written down in á¹¢alehâ€™s works. Based on this analysis, we also would provide a response to the error Geertz makes about the animistic attribute of slametan. In contrast to his imagination, slametanis perfectly Islamic and based on Islamic practice of communities from which Javanese Islam originate. In addition, Kiai Shaleh accepts the ritual and gives it Islamic justification. Meanwhile, sadjen â€“ as Kiai Shaleh points out â€“ is totally an opposition to the most fundamental credo of Islam, namely the Unity of God, â€œTauhid.â€